Intercalated nanosized MO2 (M: Sn, Ce) layers between CNTs and Pt or PtSn nanoparticles catalysts (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
Direct ethanol fuel cells (DEFCs) is receiving enormous attention as alternative electrical energy conversion systems. This paper gives an outline on some recent advances achieved in our laboratory regarding the development of high performing anode for ethanol oxidation. We developed multi-components binderless hierarchically organized layer onto layer nanostructured catalysts comprising a carbon paper (CP, current collector)/carbon nanotubes (CNTs, conductivity enhancer)/catalyst promoter (MOx, M: Sn; Ce)/Pt-based (electrocatalyst). The main focus was how to lower the onset oxidation potential (OOP) of ethanol at Pt75Sn25 catalyst. Towards that aim, metal oxides such as CeO2 and SnO2 were sought as catalyst promoters. It has been discovered that intercalating a nanostructured layer of SnO2 between CNTs and Pt75Sn25 considerably lowered the OOP of ethanol and also increased the specific mass activity (SMA) at low potentials. Indeed, the OOP at the CP/CNT/SnO2/Pt75Sn25 was 210 mV and 117 mV negative relative to that delivered by CP/CNT/Pt and CP/CNT/Pt75Sn25, respectively confirming by that the promoting effect of SnO2 of the oxidation of CO at low potentials. The SMA determined at slow potential scan rate of 5 mV/s at 0.4 V vs. Ag/AgCl revealed that CP/CNT/SnO2/Pt75Sn25 delivered an SMA of 1.2 times higher than that of the CP/CNT/Pt75Sn25 catalyst and 1.5 times greater than the one exhibited by the CP/CNT/CeO2/Pt75Sn25 catalyst.